ANALISIS PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PENINGKATAN PENDAPATAN NASABAH PELAKU USAHA MIKRO DI PT. BPR SYARIAH LUMBUNG PITI NAGARI TAEH BARUH KECAMATAN PAYAKUMBUH - Viranda Oktavia; Novera Martilova (ADISAM PUBLISHER, 2024)
The background of this research is whether there is an effect of murabahah financing on increasing the income of micro business customers at BPRS LPN Taeh Baruh Payakumbuh District. The type of data used is primary data obtained from respondents through distributing questionnaires. In taking samples using a random sampling method with a total of 76 respondents. The data analysis techniques used are validity tests, reliability tests, classic assumption tests consisting of normality tests and autocorrelation tests, simple linear regression tests, coefficient of determination tests and hypothesis tests. The results of research conducted using SPSS V 25 show that the murabahah financing variable has a significant influence on increasing income as evidenced by the results of t count (5.944) ≥ t table (1.995) and the significant value is smaller than 5%, namely (0.000) ≤ (0.05). And the results of the coefficient of determination test (R2) showed an R Square value of 0.323 or 32.3%, so it can be concluded that the variables of murabahah financing and increasing income have a weak influence with little contribution. Meanwhile, the remaining 67.7% was influenced by other factors not discussed in this research. Thus it can be concluded that H0 is rejected and Ha is accepted